Nineteen steps eaudiobook A novel. - Brown, Millie Bobby (HarperAudio, 2023)
Emmy-nominated actress and producer MILLIE BOBBY BROWN's debut novel, Nineteen Steps, is a moving tale of love, longing, and loss, inspired by the true events of her family's experience during World War II. ""My inner history-loving teenage geek clapped her hands in ecstasy at the thought of a historical novel penned by Enola Holmes, and she wasn't disappointed!"—Kate Quinn Love blooms in the darkest days... It's 1942, and London remains under constant threat of enemy attack as the second world war rages on. In the Bethnal Green neighborhood, Nellie Morris counts every day lucky that she emerges from the underground shelters unharmed, her loving family still surrounding her. Three years into the war, she's grateful to hold onto remnants of normalcy—her job as assisting the mayor and nights spent at the local pub with her best friend. But after a chance encounter with Ray, an American airman stationed nearby, Nellie becomes enchanted with the idea of a broader world. Just when Nellie begins to embrace an exciting new life with Ray, a terrible incident occurs during an air raid one evening, and the consequences are catastrophic. As the truth about that night is revealed, Nellie's world is torn apart. When it seems all hope is lost, Nellie finds that, against all odds, love and happiness can triumph. Nineteen Steps is a deeply affecting, mesmerizing page-turner inspired by the author's family history. An epic story of longing, loss, and secrets, Millie Bobby Brown's propulsive debut introduces an unforgettable, brave young woman and boldly portrays the strength in the power of love. "Inspired by my Nanny Ruth, this book is very personal and close to my heart. I grew up listening to stories about her time living through the war. I'm honored to keep her story alive."—Millie Bobby Brown